Study of Groundwater Quality in Magelang City Due to the Impact of Domestic and Industrial Waste - Muhammad Tri Aji; Abdul Qadir Jailani (Journal of Aquaculture Science, 2020)
This study aims to determine the current condition of groundwater quality in the city of Magelang due to the disposal of domestic and industrial waste. The analysis used was to measure physical, chemical, and biological parameters in situ and ex-situ. The research method used purposive sampling and then analyzed descriptively using water quality standards. The results showed that the physical parameters were still in good condition, while the values (TSS) of Total Suspended Solid and Total Dissolved Solid was 3.7 mg / L and 227.95 mg / L. On the other hand, there was a fluctuation in the pH value at several water stations which showed a tendency to be acidic. Furthermore, the nitrate levels at research stations 1,6,7 and 9 showed values that exceeded the established threshold of 10 mg/L. Furthermore, for the BOD value that has a value of more than 2 mg / L as a requirement for entering class 1, groundwater quality is safe for hygienic, Chemical Oxygen Demand has a value that exceeds the maximum requirement of 10 mg/L in all research station and is categorized as heavy pollution. The total coliform value that exceeds the water quality standard for sanitation hygiene according to Permenkes No. 32 of 2017 at 50 MPN / 100ml. The quality of groundwater in the Magelang can be used for drinking water, provided that its use must go through the cooking process first.Keywords: Groundwater quality, waste, Magelang